2015
DOI: 10.1121/1.4921270
|View full text |Cite
|
Sign up to set email alerts
|

Axial vibrations of brass wind instrument bells and their acoustical influence: Theory and simulations

Abstract: Previous work has demonstrated that structural vibrations of brass wind instruments can audibly affect the radiated sound. Furthermore, these broadband effects are not explainable by assuming perfect coincidence of the frequency of elliptical structural modes with air column resonances. In this work a mechanism is proposed that has the potential to explain the broadband influences of structural vibrations on acoustical characteristics such as input impedance, transfer function, and radiated sound. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
5
10
0
1
Order By: Relevance
“…16 has recently been extended by Kausel et al, who demonstrated theoretically how the whole-body motion of brass wind instruments can couple to the internal sound field and how this coupling can explain many of the observed effects on the radiated sound of the instrument under normal playing conditions. 19 Their results of computer modeling of a simplified trumpet indicate that this coupling is broad-band and frequency dependent, in agreement with previous experimental results. Furthermore, the results predict that whole-body motion can either increase or decrease the amplitude of the acoustic transfer function (ATF), which is defined as the ratio of the acoustic pressure in the open air in front of the bell to that in the mouthpiece.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…16 has recently been extended by Kausel et al, who demonstrated theoretically how the whole-body motion of brass wind instruments can couple to the internal sound field and how this coupling can explain many of the observed effects on the radiated sound of the instrument under normal playing conditions. 19 Their results of computer modeling of a simplified trumpet indicate that this coupling is broad-band and frequency dependent, in agreement with previous experimental results. Furthermore, the results predict that whole-body motion can either increase or decrease the amplitude of the acoustic transfer function (ATF), which is defined as the ratio of the acoustic pressure in the open air in front of the bell to that in the mouthpiece.…”
Section: Introductionsupporting
confidence: 87%
“…In what follows, we present experimental evidence of the interaction between the vibrating walls and the internal air column of a trumpet bell similar to that predicted in Ref. 19. In Sec.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…[7][8][9] Del mismo modo, casi todos los ejecutantes de estos instrumentos creen firmemente que los efectos de las vibraciones del instrumento tienen un efecto significativo en el sonido. Esto ha demostrado ser cierto en el caso de las vibraciones de la campana 10 y se ha propuesto una teoría para explicar el efecto, 11,12 pero no está claro que las vibraciones de otras partes del instrumento afecten al sonido.…”
Section: Reflexiones Finalesunclassified